If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -13 + 12h = 11 Solving -13 + 12h = 11 Solving for variable 'h'. Move all terms containing h to the left, all other terms to the right. Add '13' to each side of the equation. -13 + 13 + 12h = 11 + 13 Combine like terms: -13 + 13 = 0 0 + 12h = 11 + 13 12h = 11 + 13 Combine like terms: 11 + 13 = 24 12h = 24 Divide each side by '12'. h = 2 Simplifying h = 2
| 8x-9=-25 | | -5(x+3)=2r | | 125m-100m+38200=40600-175m | | 4x+15=-13 | | 6.3x=2.4x-3 | | -32-1=8-32 | | -x^2+20x+20=0 | | 12=a-44 | | 6.3x=2.3x-3 | | x-2=0.5x+5 | | (5+7i)+(-3-2i)= | | x+(-7)=-12 | | x-2=1.5x+5 | | -4y-2y=28 | | 2x+18+4x=2x+10 | | 11x-y=-6 | | -4x+7=12 | | 5x-(2x+5)=7 | | 2x+5y=19.5 | | -12x+28=2x-6 | | 6(x-2)+5x=6(3x-4) | | 5(3-2x)=-10x-15 | | 4x-x+12=48 | | p=7q+8r | | 9h-9=6h+3 | | -1-9a=179 | | y-34=27 | | y-34=7 | | -90=15a | | 7x-3+4x-9=-2(3x-5) | | 4(9y-5)=10(3y+17)-10 | | -62+z=-18 |